2022
DOI: 10.3390/economies10060134
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain-Based Traceability System to Support the Indonesian Halal Supply Chain Ecosystem

Abstract: The halal industry is constantly developing into a broader concept of the Islamic economy, an economic activity that follows the Islamic-based principle. As a populous Muslim country, Indonesia follows the growth trend by aiming to dominate the global halal market. The strategy is to improve the current halal assurance process. Presently, the technology and procedure do not provide enough process transparency, traceability, and granularity of information. To achieve the strategic goal, a technological change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Blockchain technology has significantly contributed to modernizing finance, gaining recognition within the banking sector for its potential to bolster transaction security and foster financial market development [20,[22][23][24][25]. Through decentralized operations, blockchain instills heightened confidence in previously centralized systems, establishing trustless networks where parties transact without relying on mutual trust [14,26]. Immutable transaction records ensure both security and transparency, driving their widespread adoption across diverse industries.…”
Section: Blockchain Technology In the Financial Industrymentioning
confidence: 99%
“…Blockchain technology has significantly contributed to modernizing finance, gaining recognition within the banking sector for its potential to bolster transaction security and foster financial market development [20,[22][23][24][25]. Through decentralized operations, blockchain instills heightened confidence in previously centralized systems, establishing trustless networks where parties transact without relying on mutual trust [14,26]. Immutable transaction records ensure both security and transparency, driving their widespread adoption across diverse industries.…”
Section: Blockchain Technology In the Financial Industrymentioning
confidence: 99%
“…Research that examines this topic is also still very little found. One of the relevant studies found is Alamsyah et al (2022) explaining the Blockchain-Based Traceability system to Support Indonesia's Halal Supply Chain Ecosystem. The halal industry continues to develop into a broader concept of Islamic economics, namely economic activities that follow Islamic-based principles.…”
Section: Cluster 2 Supply Chain Traceability In Indonesia Halal Pharm...mentioning
confidence: 99%
“…Therefore, traceability unmasks the flow of information. 46 It comes from the fact that DLT is a decentralized system where the information contained in the system is visible to all participants. 47 Every node in the DLT includes a complete record of the transactions, thus increasing the traceability of the asset’s movement.…”
Section: The Taxonomymentioning
confidence: 99%